Exploring Heterogeneity in Shrimp Farmers’ Preferences for the Contracts of Producing Certified Organic Shrimp - Tran, Duyen Thi Thu; Takahashi , Yoshifumi; Nomura, Hisako; Yabe, Mitsuyasu (Asian Journal of Agriculture and Rural Development, 2020)
This research applied choice experiments to explore farmers’ preferences for hypothetical contracts of producing certified organic shrimp. The contracts were described by four attributes, including premium for certified organic shrimp, premium-payment delay, selling place and the provision of quality seed. Conditional logit and mixed logit models were used to analyze the data which were collected among shrimp farmers in Vietnam. The results indicate that farmers prefer the contract with a higher premium; however, premium-payment delay decreases farmers’ utility and the probability of choosing the contract. Besides the premium, the provision of quality seed is an important attribute that attracts farmers to choose a contract. Almost farmers prefer to sell their shrimp from farms. The results also show heterogeneity in farmers’ preferences for the contract’s attributes and their willingness to accept these attributes. These findings should be carefully considered in building reasonable and attractive contracts for shrimp farmers.